2023
DOI: 10.1039/d2cp05525b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced charge transport across molecule–nanoparticle–molecule sandwiches

Abstract: The electrical properties of large area molecular devices consisting of gold nanoparticles (GNPs) sandwiched between a double layer of alkanedithiol linkers have been examined. These devices have been fabricated by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The presence of GNRs offers more efficient electron transport pathways in this complex, hierarchically arranged material. Therefore, the self-assembly of gold nanoparticles can be beneficial for photovoltaic devices by controlling the charge dynamics between different layers of constituent materials [44]. Similarly in ref.…”
Section: Electrical Applications Photovoltaics and Charge Dynamicsmentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of GNRs offers more efficient electron transport pathways in this complex, hierarchically arranged material. Therefore, the self-assembly of gold nanoparticles can be beneficial for photovoltaic devices by controlling the charge dynamics between different layers of constituent materials [44]. Similarly in ref.…”
Section: Electrical Applications Photovoltaics and Charge Dynamicsmentioning
confidence: 92%
“…Moreover, sandwiched molecules, nanoparticles, and molecules have been reported to exhibit superior charge transport. This is because of the combination of the electrical properties of nanoparticles and organic ligands, indicating the potential for large-area devices [44]. Electrical measurements conducted on connected GNRs via thiol end-capped oligophenylenevinylene solution for both before and after immersion in the solution, demonstrated a three-order-of-magnitude increase in conductance, highlighting molecular-mediated transport for nanoelectronics, and photonics [45].…”
Section: Cross-linking Through Moleculesmentioning
confidence: 99%
“…17 A model by Chazalviel and Allongue 18 indeed showed that electron transfer between the metal electrode and nanoparticles in a layered metal-SAM-nanoparticle structure is up to 10 12 orders of magnitude more efficient than between a redox molecule in solution and the nanoparticle. More recently, Nichols et al 19 also reported improved conductivity in SAM-nanoparticle-SAM constructs due to the unique double monolayer structure of the SAMs, enabling more efficient electron transfer pathways. Thanks to their high surface area-to-volume ratio, bound AuNPs also provide a larger electrode area for the redox process to take place, resulting in enhanced system sensitivity.…”
Section: Introductionmentioning
confidence: 99%